Transformation and expression of TMV-B MP gene in tobacco - CHEN Qing; XUE Chao-yang; WU Jun-jie; LING Jian-qun; ZHOU Xue-ping (浙江大学学报. 农业与生命科学版)
The movement protein (MP) gene of tobacco mosaic virus isolated from faba bean was amplified by RT-PCR technique with specific primers designed on the basis of reported TMV-B sequence. The cDNA fragment was cloned into pGEM-T easy vector and then sequenced. The sequence was identical with reported TMV-B MP sequence. The MP gene was inserted into plant expression vector pBI121 in viral sense [pTMP (+)] and antisense [pTMP (-)], under the control of CaMV 35S promoter. Both of pTMP (+) and pTMP (-) DNA was transformed into Nicotiana tabacum by Agrobacterium tumefaciens LBA4404. PCR, Southern dot blot, Northern dot blot and Western blot confirmed MP genes were expressed in viral sense and antisense in transgenic plants.